Shoreline Evolutionary Trends Along Calabrian Coasts: Causes and Classification - Foti, Giandomenico; Barbaro, Giuseppe; Barillà, Giuseppina Chiara; Mancuso, Pierluigi; Puntorieri, Pierfabrizio (Frontiers in Marine Science, 2022)
The issue of coastal erosion currently affects most of the world’s coastal territories. This erosion is generally caused by an alteration of coastal and river dynamics both due to the action of natural factors and to the increase in anthropogenic pressure, mainly observed in the second half of the last century after the end of the Second World War. In the future, this issue may be more affected by climate change. This paper describes the shoreline evolutionary trends at different time scale along the Calabrian coasts, a region in southern Italy, in over 50 sample areas. Calabria represents an interesting case study due to its geomorphological peculiarities and due to its considerable anthropogenic pressures, which have caused extensive erosive processes. In addition, this paper analyzes the main causes of these evolutionary trends and classifies them using a quick methodology based on a shoreline variation rate of a fixed area. This is an index-based methodology and is a part of a new generally index-based coastal risk assessment methodology, developed by the Mediterranea University of Reggio Calabria and the Calabria Region and which is currently in progress. The main result is that the sample areas in the erosion classes prevail over those in the advancement class for very long-term, long-term and middle-term time interval while for short-term and most recent time interval the sample areas in the advancement class prevail over those in the erosion classes.